Voluntary blood donation knowledge, attitude, and practice among adult populations of Hosanna Town, South Ethiopia: a community-based cross-sectional study - Mussema, Abdulhakim; Bawore, Solomon Gebre; Abebaw, Tewodros; Tadese, Wegayehu; Belayineh, Melsew; Yirga, Abel; Mohammed, Tofik; Seid, Abdurezak Mohammed (Frontiers in Public Health, 2023)
Introduction Even though blood donation has increased in the past decades, it remains a challenge worldwide. An adequate blood supply can only be assured through voluntary blood donation. There is inadequate information on the level of blood donation practice in the current study area. This study aimed to assess the knowledge, attitude, practice, and associated factors toward voluntary blood donation among Hosanna town adult populations. Methods A cross-sectional study was conducted from 1 May 2022 to 30 June 2022, on a total of 422 adult populations of Hosanna town. A simple random sampling technique was used to select the study subjects. Data were collected by face-to-face interviews using a structured pre-tested questionnaire. The levels of knowledge, attitude, and practice of participants toward voluntary blood donation were measured using a set of questions. Data were analyzed using SPSS version 25. Chi-square and odds ratios were calculated, and the results were presented with words and tables. Results In this study, a total of 422 participants enrolled with a response rate of 96.6%. Of the total respondents, 204 (48.3%), 209 (49.5%), and 123 (29.15%) study participants had good knowledge, favorable attitude, and experience of blood donation, respectively. Participants' sex being male and having favorable attitudes were found to have significant associations with blood donation practice. Furthermore, it was found that male participants were more than two and a half times more likely to donate blood than female participants (AOR: 2.53; 95% CI: 1.54, 4.15). Those who had favorable attitudes were found more than three and a half times more likely to donate blood than those having unfavorable attitudes (AOR: 3.54; 95% CI: 1.32, 9.46) Conclusion and recommendations A large proportion of adult populations had poor knowledge, unfavorable attitudes, and low practice toward voluntary blood donation. Therefore, local and national blood banks and transfusion agencies should design strategies that can be implemented to improve the knowledge or attitude of the adult population and motivate the population to donate blood voluntarily.